1985
DOI: 10.1017/s000748530001436x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on insecticide-impregnated targets for the control of riverine Glossina spp. (Diptera: Glossinidae) in the sub-humid savanna zone of Nigeria

Abstract: Insecticide-impregnated blue cotton targets 70 × 110 cm weretested for the control of Glossina palpalis palpalis (Robineau-Desvoidy) and G. tachinoides Westwood in riverine fringing forests in central Nigeria, under wet-season conditions. Following exposure to treated cloth for 1·5 min, delta-methrin caused 100% mortality of G. p. palpalis for six weeks at 0·05% and for 13 weeks at 0·1%. Dieldrin at 5% was not very effective. At 4%, endosulfan initially caused a high mortality, but rapidly lost its activity, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
1
7
0
1
Order By: Relevance
“…Some of the measures to control riverine tsetse flies include application of pyrethroid based-insecticides or 'pour-on' (Bauer et al 1995;Leak et al 1995), mass trapping (Gouteux & Lancien 1986;Takken et al 1986), chemical insecticide-impregnated traps or targets (Laveissière & Couret 1981Oladunmade et al 1985), and sterile insect technique (SIT) (Politzar & Cuisance 1982;Takken et al 1986;Oladunmade et al 1990). …”
Section: Introductionmentioning
confidence: 99%
“…Some of the measures to control riverine tsetse flies include application of pyrethroid based-insecticides or 'pour-on' (Bauer et al 1995;Leak et al 1995), mass trapping (Gouteux & Lancien 1986;Takken et al 1986), chemical insecticide-impregnated traps or targets (Laveissière & Couret 1981Oladunmade et al 1985), and sterile insect technique (SIT) (Politzar & Cuisance 1982;Takken et al 1986;Oladunmade et al 1990). …”
Section: Introductionmentioning
confidence: 99%
“…These data are in accordance with earlier differential equation models that showed that, for pest species with a low fertility rate and a high survivorship such as tsetse flies, the combination of sterile insects (effective at low densities) and traps (very effective at high densities) is most efficient (Barclay and van den Driessche 1989). Results obtained in operational AW-IPM programs with an SIT component are testimony to this, although the release of sterile males was preceded in Tanzania (Williamson et al 1983a, b) with SAT, and in Nigeria (Oladunmade et al 1985), Burkina Faso (Politzar and Cuisance 1984) and Unguja Island (Vreysen et al 2000) with ITL or TT and not used simultaneously.…”
Section: Discussionmentioning
confidence: 98%
“…For riverine species, the density of traps/targets is expressed in number of traps/targets per linear km in the sub-humid areas where the flies are confined to gallery forests. Target/trap densities of 7-10 per linear km were usually used against G. palpalis in those areas (Politzar and Cuisance 1984;Oladunmade et al 1985). However, in the more humid areas of West Africa, riverine species are often not strictly riverine anymore and their distribution becomes more ubiquitous, requiring much higher trap densities.…”
Section: Discussionmentioning
confidence: 99%
“…They point out that SIT may be the only way to clean up isolated populations or populations that have only those ßies remaining that are not attracted to targets or baits. They also point to successful Þeld operations (Politzar and Cuisance 1984;Oladunmade et al 1985Oladunmade et al , 1990Vreysen et al 2000). Those who see SIT as unnecessary, for example, Molyneux (2001) argue against SIT as a continent-wide eradication strategy and allow these arguments spill over into a general dismissal of SIT as a component of integrated area-wide control.…”
Section: Case Study: Using Simulation Models To Advise Tsetse Controlmentioning
confidence: 99%